Detection of Histamine and Tyramine in some Cheese - Thannae M. Amine (Journal of High Institute of Public Health, 2007)
The biogenic amines content of various food has been widely studied because of their potential toxicity. This study aims at presenting data about histamine and tyramine content in some locally and imported soft, hard, and semihard cheese available in Alexandria markets throwing lights on its public health hazard. A total of 140 random cheese samples included a large variety of types of soft cheese (kareish, old cheese (Mish), Demietta), Semihard cheese, (Roquefort and Gouda), and hard cheese (Ras and Cheddar) as twenty samples of each were analysed for histamine and tyramine using high performance liquid chromatography (HPLC). Results showed that histamine and tyramine were detected in (35–55%) and (70-100%) of samples, respectively. All examined samples contained histamine level lower than the critical oral dose toxic to human (100 mg/100 g). Tyramine exceeded the dangerous dose for patients receiving MAOI, (6 mg) by the percentage of (30, 100, 60, 100, 50, 80, and 60%), respectively. Histamin concentration increased in the order of cheddar > Mish> Gouda>Demietta> Ras > Roquefort > Kareish cheese. Also, tyramine increased in these manner Roquefort > Cheddar > Mish > Demietta > Gouda > Kariesh. The highest level of histamine and tyramine (20.46±7.73 and 32.76±10.32 mg/100g) recorded in cheddar and Roquefort cheese, respectively but the lowest level showed in kareish cheese (4.02±1.74 and 7.12±3.75 mg/100 g) of histamine and tyramine, respectively.